Peran Perempuan pada Masa Kesultanan Wanita Turki Ottoman - Siti Ameliya; Bella Amelia; Aditya Firmansyah; Maftuh Sujana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
During the era of the Sultanate of Women in the Ottoman Empire, women played a significant role in politics, governance, and various social and cultural fields. Figures such as Hafsa Sultan, Hürrem Sultan, Mihrimah Sultan, Kösem Sultan, and Turhan Sultan were not merely the mothers or wives of sultans, but leaders who held considerable influence in the political decision-making and administration of the empire. Through their positions as Valide Sultan or other royal family members, these women managed to influence both internal and external policies, as well as initiate numerous social and cultural projects. This paper aims to explore the roles of women during the Sultanate of Women, analyzing their impact on the political and social structure of the empire, and highlighting the legacy they left in Ottoman history. Using a historical and analytical approach, this study provides a deeper understanding of how women, despite living in a patriarchal system, were able to play powerful roles in politics and social development.